2022
DOI: 10.5272/jimab.2022284.4676
|View full text |Cite
|
Sign up to set email alerts
|

ASSESSMENT OF THE BIOACCUMULATION OF MICROPLASTICS IN THE BLACK SEA MUSSEL Mytilus galloprovincialis L., 1819

Abstract: The accumulation of microplastics in the world oceans is one of the main global problems of the modern world. The Black Sea is the main source of seafood for people from several countries, including Bulgaria. The pollution of the Black sea is a result of various factors, especially anthropogenic. The aim of this study was to determine the presence and accumulation of microplastics in the Black Sea mussel Mytilus galloprovincialis L., 1819, harvested from different locations along the northern Bulgarian Black S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…On the other hand, the weight of these particles increases due to the accumulation of marine plants and nutrients in them and this can affect the distribution of plastics and their sedimentation on the sea bed. In studies on the black mussel, it was reported that these polymers are dominant in the mussels (Ibryamova et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the weight of these particles increases due to the accumulation of marine plants and nutrients in them and this can affect the distribution of plastics and their sedimentation on the sea bed. In studies on the black mussel, it was reported that these polymers are dominant in the mussels (Ibryamova et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…To identify the polymer, we used FTIR spectroscopy according to Ibryamova et al (2022). All results were done in triplicate.…”
Section: Polymer Identificationmentioning
confidence: 99%
“…On the other hand, the weight of these particles increases due to the accumulation of marine plants and nutrients on them, and this can affect the distribution of plastics and their sedimentation on the seabed [41]. In studies on the black mussel was reporeted, that these polymers are dominant in the mussels [42].…”
Section: Discussionmentioning
confidence: 99%
“…To identify the polymer we used FTIR spectroscopy according to [27]. All results were done in triplicate.…”
Section: Polymer Identificationmentioning
confidence: 99%